Bichromophoric anticancer drug: Targeting lysosome with rhodamine modified cyclometalated Iridium(III) complexes. (March 2019) - Ma, Wenli; Ge, Xingxing; Guo, Lihua; Zhang, Shumiao; Li, JuanJuan; He, Xiangdong; Liu, Zhe
Abstract: Four bichromophoric cyclometalated iridium complexes were synthesized and fully characterized. Their antiproliferative capacity against A549, HepG2 cells and HeLa cells as well as two human normal cells was studied by MTT assay. Rhodamine B modified complexes2 and4 were not cytotoxic to A549 cells while both rhodamine 6 g modified complexes1 and3 showed greater cytotoxicity than cisplatin. In particular, the antiproliferative activity of complex3 was about 4.6 times than that of cisplatin. Thus, complex3 was used for stability and pH sensitivity studies. The results indicated that the complex not only had rich fluorescence properties under acidic conditions, but also showed good stability. Further, interaction of complex with bovine serum albumin (BSA) has been investigated by UV−vis, fluorescence, synchronous fluorescence spectroscopy. The complexes have a certain ability to bind the BSA. Interestingly, these complexes can catalyze the reaction of the coenzyme NADH to NAD +, which is consistent with the apparent growth of ROS in cells. In addition, complex3 can cause S phase arrest in the cell cycle, induce apoptosis, and affect mitochondrial membrane potential changes. Localization experiments of intracellular complexes by confocal microscopy suggested that these complexes enter cancer cells through energy dependence and specifically target the lysosomes, thus resulting in the damage of lysosomes. Graphical abstract: Synthesis and characterization of four rhodamine-modified bichromophoric cyclometalated iridium(III) complexes. Flow cytometry and confocal microscopy were used to study the specific anti-proliferative ability, subcellular localization of the complexes, the way the complex entered the cell and the lysosomal damage. Highlights: Synthesis and characterization of four rhodamine-modified bichromophoric cyclometalated iridium (III) complexes, and by introducing the fluorophore-rhodamine, the fluorescence intensity of the complex is adjustable, and the fluorescence intensity is stronger under acidic conditions. By adjusting the ligand, complexes 1 and 3 have better anticancer activity than cisplatin. The complex can be successfully localized in lysosomes and further affect apoptosis by disrupting lysosomes.